The impact of the Arabic language on the Arabic language (Journal of the College of Basic Education, 2022)
Contemporary linguistic studies have focused on the subject of translation between different languages ​​for the exchange of general sciences and cultures in order to see what other nations and peoples have reached. In order to identify the impact of the Arabic language on the English language, this research focused on comparing and analyzing between English and Arabic words, striving to find the largest possible number that could be entered from Arabic into English. This research contained three topics: the first is related to defining the subject of the research with a historical idea of ​​the civilizational interaction that resulted in the exchange of vocabulary and information between nations such as the Arabs and the West. The second research